Effect of structured OM chanting and listening on cognitive functions in young adults - Venkatesha, Padmanabha Baburayanakoppulu; Khalid, Jabir Padathpeedika; Goothy, Sai Sailesh Kumar; Sathianesan, Bethiun; Rajagopalan, Vijayaraghavan; Kurien , Mukkadan Joseph (Journal of Bangladesh Society of Physiologist, 2025)
Background: OM chanting was reported to improve parasympathetic activity and offer relaxation. This is due to the vibration effect created during the chanting of OM. There is a need to motivate medical students to practice and implement yoga and meditation to overcome the stress they face during their course. This also helps to improve cognitive functions and helps them to develop their academic performance as well. Objectives: To investigate the impact of Om chanting on cognitive abilities of healthy young adults. Methods:This experimental study was carried out on 40 young healthy volunteers aged 18-24 years, both male and female. After obtaining voluntary, written, informed consent 20 subjects were randomly assigned to experimental group and 20 were control. The experimental group received an initial training in structured Om chanting and then performed OM chanting daily for 12 weeks. The control participants were not under OM for this 12 weeks of follow up period. Both before and after the intervention, the control and intervention groups were assessed for their cognitive abilities by spatial and verbal memory test and Generalized Anxiety Disorder score (GAD-7). Statistical analysis was done by students un paired t test. Results: Demographic data of the participants was not significantly different when compared between the control and experimental groups. Spatial, verbal memory scores and GAD-7 scores were almost similar in both control and intervention groups at baseline. Significant improvement was observed in the spatial and verbal memory scores and significant decrease in the anxiety scores was also observed in the experimental group participants after 10 weeks of OM chanting. Conclusion: Structured OM chanting may be effective to increase cognitive functions and reduce anxiety in young healthy volunteers. J Bangladesh Soc Physiol 2024;19(1): 23-28